Inovação Sustentável em uma Organização de Saúde - Cristiane Froehlich (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
This article aims to verify if the innovations institutionalized in a health organization can be considered as sustainable innovations. To meet this objective, a qualitative case study was carried out, with descriptive characteristics, the object of which was a large private hospital, located in the city of Porto Alegre-RS. Data were collected through nine semi-structured interviews with the leaders indicated by the Institution and data were analyzed through qualitative content analysis. The main results show that the health organization studied develops innovation practices that contribute to sustainability, such as: acquisition of equipment, innovation in the management model, innovation in the organizational structure and the introduction of the School of Health. Occurred in a systematized manner according to the sustainability pillars and, rather, from a strategic conception with significant economic and social benefits aligned with the management model.